Low‐Cost, Scalable, and Reusable Photothermal Layers for Highly Efficient Solar Steam Generation and Versatile Energy Conversion. (25th February 2020) - Shan, Xiaoli; Zhao, Aiqing; Lin, Yawen; Hu, Yujing; Di, Yunsong; Liu, Cihui; Gan, Zhixing
Abstract: Solar steam generation (SSG) based on the photothermal effect has been considered to be a promising avenue for freshwater production. However, the fabrication of highly‐efficient photothermal layers, at large‐scale and low‐cost is still a challenge, hindering practical applications. Herein, it is demonstrated that carbonized towel‐gourd sponges (CTGS) are excellent photothermal materials. And a capillarity‐driven interfacial self‐coating method is developed to prepare the super‐hydrophilic CTGS/paper photothermal layer. The SSG device based on the CTGS/paper exhibits a high evaporation rate of 1.53 kg m −2 h −1 with an efficiency of 95.9% under 1 sun irradiation. The high evaporation rate only slightly reduces when confronting the diverse and complex practical SSG conditions, such as seawater and waste water. Moreover, CTGS/paper has the advantages of simple preparation, recyclablability, low‐cost (≈4 $ per m 2 ), high‐efficiency, flexibility, and scalability, which are the important prerequisites for promoting SSG techniques for industrialization and practical applications. In addition, the versatile energy conversion ability of the CTGS/paper is also demonstrated. Assisted by the photothermal effect of CTGS/paper, solar energy is converted to mechanical energy and electricity. Abstract : A capillarity‐driven interfacial self‐coating method is developed to prepare a super‐hydrophilic carbonized towel‐gourd sponges (CTGS)/paper photothermal layer. The solar‐steam generation (SSG) device based on the CTGS/paper exhibits a high evaporation rate of 1.53 kg m −2 h −1 with an efficiency of 95.9% under 1 sun irradiation. In addition, the versatile energy conversion ability of the CTGS/paper is also demonstrated.